2016
DOI: 10.1007/s00259-016-3533-z
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term follow-up and role of FDG PET in advanced pancreatic neuroendocrine patients treated with 177Lu-D OTATATE

Abstract: Both FA and RA are active in patients undergoing Lu-PRRT. However, an FA of 27.8 GBq of Lu-PRRT prolongs PFS and OS compared to an RA of 18.5 GBq. Our results indicate that FDG PET is an independent prognostic factor in this patient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 30 publications
7
97
1
Order By: Relevance
“…On the other hand, 18 F-FDG imaging (FDG-PET) has traditionally been used for staging poorly-differentiated G3 tumors, or to complement SRI in well-differentiated NET when Ki67 exceeds 10% 6. However, there are arguments for a wider use of dual-tracer imaging (SRI-PET + FDG-PET) in well-differentiated NET, as recent studies underscored the prognostic value of FDG-PET in these patients 10-15.…”
mentioning
confidence: 99%
“…On the other hand, 18 F-FDG imaging (FDG-PET) has traditionally been used for staging poorly-differentiated G3 tumors, or to complement SRI in well-differentiated NET when Ki67 exceeds 10% 6. However, there are arguments for a wider use of dual-tracer imaging (SRI-PET + FDG-PET) in well-differentiated NET, as recent studies underscored the prognostic value of FDG-PET in these patients 10-15.…”
mentioning
confidence: 99%
“…However, we believe that liver metastases, age and tumor burden carry greater weight as prognostic factors and predictors of response after PRRT than SRI uptake value [1]. Given that FDG PET and SRI may be discordant for some lesions, we agree that a divergence of tracer uptake in FDG PET and SRI must not be ignored.…”
mentioning
confidence: 92%
“…
Dear Sir, We would like to thank Zanotti-Fregonara et al for their interesting letter about our recent study, BLong-term follow-up and role of FDG PET in advanced pancreatic neuroendocrine patients treated with 177Lu-DOTATATE^, published in the March 2017 issue [1]. In addition to the positive comments on the importance of dual-tracer imaging, Zanotti-Fregonara et al raise the question as to whether the uptake level in somatostatin receptor imaging (SRI) plays a role in predicting response to peptide receptor radionuclide therapy (PRRT).
…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…PROMID, CLARINET, RADIANT-4, NETTER-1, TELESTRA, and SPINET). Unfortunately, there are no results of prospective studies using PRRT in pancreatic NETs available yet; in some published studies on the effectiveness of PRRT in this group of patients, the observed PFS is 29.7-39 months, and OS is 53-70 months [242][243][244][245].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%